Ityoṗyawinnät and Addis Abäba’s Popular Music Scene - Marye, Hewan Semon (Aethiopica, 2019)
The production, consumption, and distribution of contemporary Ethiopian music has thus far remained largely unexplored, although it is an important part of the urban Ethiopian public sphere. This study explores themes dominant in the music scene of Ethiopia in 2016, in which musicians explore ideas central to Ethiopian socio-political and economic life. The subversive nature of Ethiopian music, its presentation of characteristic topics of urban life, its aesthetic power, and the prominence it gives to important themes such as citizenship, nationalism, and identity are all investigated in this article. The study examines the influence music has had on bringing Ethiopians together in the face of a divisive political landscape, and as ultimately having played a critical role in the political changes the country witnessed in 2018.